Seasonal variation of fatty acids composition of milk from grazing ewes in Thessaly, central Greece - GOVARI, M.; ILIADIS, S.; PAPAGEORGIOU, D.; FLETOURIS, D. (Journal of the Hellenic Veterinary Medical Society, 2019)
The aim of this work was to evaluate the changes in fatty acids (FAs) profile and conjugated linoleic acid (CLA) concentration of milk from grazing ewes in winter (December and January) and spring (April and May) in Thessaly, central Greece. No significant changes (P>0.05) in the physicochemical properties (pH and protein, lactose and total solids content) of winter and spring milk were observed. However, the fat content of spring milk was lower (P<0.05) than the winter milk. The saturated FAs content of milk was not significantly changed (P>0.05) during winter neither during spring, whereas the polyunsaturated FAs content was significantly changed (P<0.05) in each of the four months examined. Nevertheless, in the ovine milk of spring, the saturated FAs content was significantly decreased (P<0.05), but the monounsaturated and polyunsaturated FAs content was significantly increased (P<0.05) as compared to that of winter milk. In contrast to the saturated FAs decrease in spring milk, the saturated stearic acid (C18:0) content showed a significant increase (P<0.05) in the spring milk as compared to winter milk. In winter milk, the C18:2 cis-9, trans-11 CLA levels were 0.89±0.05 and 0.98±0.03g/100 g Fatty Acid Methyl Esters (FAMEs) in December and January, respectively, whereas, in spring milk, the CLA levels were significantly increased (P<0.05) to 1.36±0.04 and 1.27±0.03g/100 g FAMEs in April and May, respectively. The atherogenicity index (AI) associated with proatherogenic and antiatherogenic FAs was found significantly (P<0.05) lower in spring milk compared to winter milk.